Toxicological and biochemical characterizations of AChE in phosalone-susceptible and resistant populations of the common pistachio psyllid, Agonoscena pistaciae - Alizadeh, Ali (Oxford University Press, 2014)
The toxicological and biochemical characteristics of acetylcholinesterases (AChE) in nine populations of the common pistachio psyllid, Agonoscena pistaciae Burckhardt and Lauterer (Hemiptera: Psyllidae), were investigated in Kerman Province, Iran. Nine A. pistaciae populations were collected from pistachio orchards, Pistacia vera L. (Sapindales: Anacardiaceae), located in Rafsanjan, Anar, Bam, Kerman, Shahrbabak, Herat, Sirjan, Pariz, and Paghaleh regions of Kerman province. The previous bioassay results showed these populations were susceptible or resistant to phosalone, and the Rafsanjan population was most resistant, with a resistance ratio of 11.3. The specific activity of AChE in the Rafsanjan population was significantly higher than in the susceptible population (Bam). The affinity ( KM ) and hydrolyzing efficiency ( Vmax ) of AChE on acetylthiocholine iodide, butyrylthiocholine iodide, and propionylthiocholine odide as artificial substrates were clearly lower in the Bam population than that in the Rafsanjan population. These results indicated that the AChE of the Rafsanjan population had lower affinity to these substrates than that of the susceptible population. The higher Vmax value in the Rafsanjan population compared to the susceptible population suggests a possible over expression of AChE in the Rafsanjan population. The in vitro inhibitory effect of several organophosphates and carbamates on AChE of the Rafsanjan and Bam populations was determined. Based on I50, the results showed that the ratios of AChE insensitivity of the resistant to susceptible populations were 23 and 21.7-fold to monocrotophos and phosphamidon, respectively. Whereas, the insensitivity ratios for Rafsanjan population were 0.86, 0.8, 0.78, 0.46, and 0.43 for carbaryl, eserine, propoxur, m-tolyl methyl carbamate, and carbofuran, respectively, suggesting negatively correlated sensitivity to organophosphate-insensitive AChE. Therefore, AChE from the Rafsanjan population showed negatively correlated sensitivity, being insensitive to phosphamidon and monocrotophos and sensitive to N -methyl carbamates.